2014
DOI: 10.1209/0295-5075/108/67001
|View full text |Cite
|
Sign up to set email alerts
|

Non-collinear antiferromagnets and the anomalous Hall effect

Abstract: The anomalous Hall effect is investigated theoretically for the non-collinear antiferromagnetic order of the hexagonal compounds Mn3Ge and Mn3Sn using various planar triangular magnetic configurations as well as unexpected non-planar configurations. The former give rise to anomalous Hall conductivities (AHC) that are found to be extremely anisotropic. For the planar cases the AHC is connected with Weyl-points in the energy-band structure, which are described in detail. If this case were observable in Mn3Ge, a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
300
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(316 citation statements)
references
References 30 publications
15
300
1
Order By: Relevance
“…This effect is closely related to the anomalous Hall effect predicted in the same class of materials [2,3], both of which are dictated by the absence of certain crystal symmetries. The appearance of magneto-optic effects in antiferromagnets is of intrinsic interest, since it would allow direct detection of the magnetic order and therefore could be useful for antiferromagnets-based memory devices [4].While non-collinear antiferromagnets have been the focus of recent interest [1][2][3], in this Letter we show that magneto-optic effects can also exist in the more commonly available collinear antiferromagnets. We start by analyzing the general symmetry requirements for magneto-optic effects, and demonstrate the symmetry principles by constructing a tight-binding model with a collinear Néel type order.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…This effect is closely related to the anomalous Hall effect predicted in the same class of materials [2,3], both of which are dictated by the absence of certain crystal symmetries. The appearance of magneto-optic effects in antiferromagnets is of intrinsic interest, since it would allow direct detection of the magnetic order and therefore could be useful for antiferromagnets-based memory devices [4].While non-collinear antiferromagnets have been the focus of recent interest [1][2][3], in this Letter we show that magneto-optic effects can also exist in the more commonly available collinear antiferromagnets. We start by analyzing the general symmetry requirements for magneto-optic effects, and demonstrate the symmetry principles by constructing a tight-binding model with a collinear Néel type order.…”
mentioning
confidence: 54%
“…While non-collinear antiferromagnets have been the focus of recent interest [1][2][3], in this Letter we show that magneto-optic effects can also exist in the more commonly available collinear antiferromagnets. We start by analyzing the general symmetry requirements for magneto-optic effects, and demonstrate the symmetry principles by constructing a tight-binding model with a collinear Néel type order.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The inverse triangular spin structure for Mn 3 Sn reduces the lattice symmetry from six-fold to two-fold in the plane and thus based on the symmetry argument, the Hall effect may appear in the ab-plane 10,31 . Indeed, a recent calculation found that Mn 3 Sn may have a large anomalous Hall conductivity 20 , which can be estimated by integrating the Berry curvature of the occupied bands over the entire Brillouin zone 9 . More recently, the possibility of a Weyl metal has been proposed, where the bands crossing E F have several Weyl points, around which the Berry curvature diverges 11 .…”
mentioning
confidence: 99%
“…Here we attack these issues in the family of noncollinear antiferromagnets including Mn 3 Sn and Mn 3 Ge, for which a strong AHE was predicted and then experimentally verified to exist [19][20][21]. First principles calculations further indicate that in Mn 3 Sn and Mn 3 Ge there are Weyl nodes around the Fermi level [22,23]. We argue that these materials possess a hierarchy of energies scales which permits a description of the microstructure and spin dynamics as an XY model with Z 6 anisotropy.…”
mentioning
confidence: 99%